(untitled) (American Journal of Islam and Society, 2014)
Roel Meijer’s edited Global Salafism: Islam’s New Religious Movement, one of the first collected works to broadly analyze contemporary Salafism as a global religious movement for English-speaking audiences, presents this movement as a string of methods for approaching Islam’s canonical sources. Its many methodological ambiguities and tactical classifications enable it to incorporate a variety of local and international religious groups: those that reject political participation (e.g., “Scholastic Salafis”), embrace their society’s established political rules (e.g., “Sahwah Movement”), and seek radical transformation often through violent means (e.g., “al-Qaeda”). In part, Salafism symbolizes a varied scholarly attempt to disentangle long-simmering questions about conservative forms of Muslim activism, most of which concern the ethics of how Muslims are to conduct their lives, perceive their individual and group identities, and understand the pious order of political and social arrangements. The volume has two primary goals: (1) to reveal the diversity among the movement’s various groups and streams and (2) to reclaim the study of Salafism from the field of security studies, which has, since 2001, influenced much of our overall understanding of this rather new religious phenomenon. The contributors challenge the widespread notion of Salafism as an exclusively violent and intransigent Islamic movement by addressing the tensions between basic Salafi doctrines (e.g., scriptural literalism, a sharp distinction between in- and outsiders, and an active program for individual and communal reform), its supposed attraction to growing numbers of Muslims, and its intrinsic links to politics as well as to violence. The contributors argue that these tensions have produced a whole range of consequences for primarily Muslim ...